A Complete Experimental Investigation on The Rheological Behavior of Silver Oil Based Nanofluid. Issue 3 (12th January 2016) - Aberoumand, Sadegh; Jafarimoghaddam, Amin; Aberoumand, Hossein; Javaherdeh, Kourosh
Abstract : In this study, thermo‐physical properties including thermal conductivity, viscosity, density and specific heat capacity of an oil based nanofluid including silver as to be nanoparticles have been experimentally studied. The results indicate an enhancement in thermal conductivity which was depended on bulk temperature and volume fraction of utilized nanofluids. Viscosity data show a significant increment through volume fraction increasing. In addition, the specific heat capacity and density of nanofluids were studied experimentally and it was found that, all measured rheological properties of these nanofluids, were not in agreement to published correlations.